Thrombocytopenia is more Frequent in Gram negative Neonatal Septicemia - Eman Abobakr Abd Alazem; Eman Abdel Ghany; Sara Abdelgayed Zaky; Marwa Abd Elhady (Cairo University, Faculty of Medicine, Department of Pediatrics, 2022)
Background: Sepsis is one of the major causes of neonatal thrombocytopenia. Aim of the work: To identify the frequency, severity, and clinical outcome of thrombocytopenia associated with culture-proven neonatal septicemia in the Neonatal Intensive Care Units (NICUs) of Cairo University Children's Hospitals. Methods: We conducted a retrospective cohort study that included all neonates with culture-proven sepsis and thrombocytopenia who were admitted to the NICUs over a one-year period (from January 2017 to December 2017). Thrombocytopenia was defined as platelet count less than 150x103/µL. The thrombocytopenic neonates were divided into two groups according to the type of cultured bacteria (gram-positive and gram-negative). Both groups were compared regarding maternal and neonatal risk factors, onset and severity of thrombocytopenia, complications, and patient survival. Results: A total of 316 out of 2172 (total number of NICU admissions) newborns were found to have culture proven-sepsis (14.5%). The frequency of thrombocytopenia in neonates with culture proven-sepsis was 30.3% (n = 96/316). Prematurity is a risk factor for early onset sepsis with thrombocytopenia (p= 0.001). The frequency of severe thrombocytopenia is more in gram-negative sepsis than that in gram-positive sepsis at the onset of sepsis and at the lowest platelet count (p= 0.014, 0.015) respectively. The frequency of hemorrhage in neonates with sepsis and thrombocytopenia was 20.8 % (n = 20/96) and it was mainly pulmonary hemorrhage 10.4 % (n=10). The overall mortality among the study group was 40.6% (n=39/96), with a higher mortality rate (46.3%) in gram-negative sepsis with thrombocytopenia (OR 2.65, p= 0.042). Conclusion: Neonatal thrombocytopenia is a common finding in neonatal sepsis, and the frequency of severe thrombocytopenia is more in gram negative sepsis. Pulmonary hemorrhage is a common type of bleeding in thrombocytopenic neonates with sepsis. Gram-positive sepsis associated thrombocytopenia has a better prognosis than gram-negative sepsis.